SUSTAINABLE AND GREEN IT BUSINESS MODELS: A SYSTEMATIC LITERATURE REVIEW ON STRATEGIES AND IMPLEMENTATION - Ridwan Ridwan; Jhon Veri (Smart Education, 2025)
Abstract: This study aims to systematically review strategies and implementation practices of sustainable and green information technology (IT) business models using the PRISMA method. Articles from Scopus, IEEE, and ScienceDirect from 2019 to 2025 were searched using keywords related to green IT business models, sustainability, and digital transformation. The review process followed the PRISMA protocol, involving identification, screening, eligibility, and inclusion stages. The findings show that sustainable IT business strategies include data center optimization, renewable energy utilization, hardware circular economy, and the integration of sustainability within digital platform business models. However, challenges such as high initial costs, technological gaps, and organizational awareness remain in implementation. This study offers a comprehensive mapping of research trends, best practices, and recommendations for developing sustainable IT business models in the era of digital transformation. Keyword: green IT; sustainable business model; PRISMA; digital transformation; systematic review. Abstrak: Penelitian ini bertujuan untuk meninjau secara sistematis strategi dan praktik implementasi model bisnis teknologi informasi (TI) yang berkelanjutan dan ramah lingkungan menggunakan metode PRISMA. Artikel dari Scopus, IEEE, dan ScienceDirect tahun 2019 hingga 2025 ditelusuri dengan kata kunci terkait green IT business model, sustainability, dan transformasi digital. Proses peninjauan mengikuti protokol PRISMA dengan tahap identifikasi, screening, eligibility, dan inclusion. Hasil penelitian menunjukkan bahwa strategi model bisnis TI berkelanjutan meliputi optimasi pusat data, penggunaan energi terbarukan, circular economy perangkat keras, dan integrasi sustainability dalam model bisnis platform digital. Namun, implementasi masih menghadapi tantangan seperti biaya awal yang tinggi, kesenjangan teknologi, dan kesadaran organisasi. Penelitian ini menyediakan pemetaan tren penelitian, praktik terbaik, dan rekomendasi pengembangan model bisnis TI berkelanjutan pada era transformasi digital. Kata kunci: green IT; model bisnis berkelanjutan; PRISMA; transformasi digital; tinjauan sistematis.